Assessing ISO 14001:2015 compliance in Iraqi healthcare: A comparative study of environmental management in public and private hospitals - Huda Sattar Jabbar; Ghada Ibrahim; Nadine Al-Khatib; Soumaya Kaakour; Alissar Yassin Haddad (Problems and Perspectives in Management, 2025)
Erratum: the name and affiliation"Huda Jabbar, MBA, Department of Management, Middle Technical University in Baghdad; Jinan University, Iraq."have been corrected to the accurate version:"Huda Sattar Jabbar, MBA, Middle Technical University, Baghdad, Iraq."This correction was made on 30 July 2025 and was not included in the original publication prior to this date. However, this was the correct affiliation at the time of publication and remains so.The online version of the article has been updated accordingly. Abstract The implementation of environmental management systems is increasingly recognized as essential for advancing sustainability in healthcare, particularly in resource-constrained contexts such as Iraq. This study evaluates the compliance of Iraqi public and private hospitals with ISO 14001:2015 standards, revealing significant discrepancies between the two sectors. Utilizing a quantitative descriptive approach, data were collected through field surveys, structured interviews, and document analysis to assess environmental management systems practices. Private hospitals demonstrated a compliance rate of 75%, while public hospitals achieved a compliance rate of only 50%. Key deficiencies in public hospitals were identified in operation (78% gap) and improvement (73% gap), indicating systemic weaknesses. Although private hospitals performed better, they still exhibited notable gaps, particularly in leadership and performance evaluation, both at 29%. Challenges common to both sectors included insufficient resource allocation, limited environmental awareness, and inadequate leadership involvement. These findings underscore the urgent need for targeted interventions to address barriers to adoption of environmental management systems. Strategies such as fostering stronger leadership commitment, optimizing resource allocation, incorporating advanced environmental technologies, and implementing ongoing staff training are recommended to bridge the compliance gap. This study provides critical insights into enhancing environmental performance and promoting sustainable healthcare practices in Iraq. Furthermore, it serves as a reference for addressing similar challenges in developing countries, emphasizing the importance of aligning healthcare operations with international environmental management standards. Acknowledgment The authors wish to convey their sincere appreciation to the two selected hospitals for their cooperation and willingness to participate in this study. The provision of necessary documentation and the allocation of time by these institutions have been invaluable in facilitating the completion of the research.